Disrupting the Gender Institution: Consciousness-Raising in the Cocoa Value Chain. Issue 9 (September 2018) - McCarthy, Lauren; Moon, Jeremy
Gender is one of the most taken-for-granted institutions. Inequality is a common by-product of this institution and questions arise as to how such inequalities can be addressed. We uncover the cognitive and emotional processes individuals experience that enable them to begin disrupting the gender institution, within our case context of a gender equality programme in the Ghanaian cocoa value chain. We identify four elements of institutional apprehension: theorizing, auditing, relating to others and exploring difference. These processes help individuals 'see' the dimensions of the gender institution: its order's laws and rules, its organizational gender regimes, and its gendered practices in daily interactions. Furthermore, some individuals are able to appreciate the dynamic interplay between these dimensions, and the power relations that are inherent within them. We argue that this fifth element of institutional apprehension, consciousness-raising, is particularly important for achieving equality. Consciousness-raising involves connecting everyday practices with organizational and structural rules, thus making 'the personal political'. It enables individuals to reconsider the way that power plays out in relational ways within value chains, promoting variously fatalism, resistance and the possibility of more multidimensional solutions to gender inequality.